2018
DOI: 10.3897/zookeys.739.20628
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide SNP data and morphology support the distinction of two new species of Kovarikia Soleglad, Fet & Graham, 2014 endemic to California (Scorpiones, Vaejovidae)

Abstract: Morphologically conserved taxa such as scorpions represent a challenge to delimit. We recently discovered populations of scorpions in the genus Kovarikia Soleglad, Fet & Graham, 2014 on two isolated mountain ranges in southern California. We generated genome-wide single nucleotide polymorphism data and used Bayes factors species delimitation to compare alternative species delimitation scenarios which variously placed scorpions from the two localities with geographically adjacent species or into separate lineag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Detailed phylogeographic studies of wide‐ranging scorpion species continue to discover that scorpions found across large areas and diverse habitat types often represent cryptic complexes of more stenotypic species (Bryson et al, , ; Habel et al, ; Parmakelis et al, ; Sousa et al, ). Such is the case for the Mesobuthus caucasicus complex (Fet et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed phylogeographic studies of wide‐ranging scorpion species continue to discover that scorpions found across large areas and diverse habitat types often represent cryptic complexes of more stenotypic species (Bryson et al, , ; Habel et al, ; Parmakelis et al, ; Sousa et al, ). Such is the case for the Mesobuthus caucasicus complex (Fet et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our second aim (2) was to test the hypothesis that divergence influenced by the Amu Darya River was simultaneous in other co-distributed species, for example potentially caused by a single vicariant event, such as initial establishment of a stable river causeway or increased flow rates. Our third goal (3) was to use genetic data to determine whether M. gorelovi contains any additional cryptic diversity, as the discovery of cryptic species is a common outcome in phylogeographic studies of scorpions (Bryson et al, 2013;Bryson, Wood, Graham, Soleglad, & McCormack, 2018;Fet, Graham, Webber, & Blagoev, 2014;Gantenbein, Fet, & Barker, 2001;Gantenbein, Soleglad, Fet, Crucitti, & Fet, 2002;Habel et al, 2012;Parmakelis, Kotsakiozi, Stathi, Poulikarakou, & Fet, 2013;Sousa, Froufe, Alves, & Harris, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…16). Another "micro-vaejovid" apparently restricted to the same orographic system (Kovarikia savaryi Bryson, Graham & Soleglad, 2018) was recently described and thoroughly discussed by Bryson et al (2018). The only species of the genus that remains currently characterized as having a wide geographical distribution is Catalinia andreas.…”
Section: Systematicsmentioning
confidence: 99%